The Archaeological Excavations in the Castel Corno Caves (Isera, Trento, Italy) : Burial Places and Settlement of a Small Alpine Community Between the 25th and 17th Centuries BC. - Battisti, Maurizio (Archaeopress, 2022)
This book presents the results of two different excavation campaigns in a prehistoric archaeological site in a deep cave in Trentino Alto Adige (Castel Corno, Isera, Trento, Italy). The excavations uncovered a number of Early Bronze Age tombs deep in the cave and, outside, the remains of a settlement.